2020
DOI: 10.1097/mjt.0000000000000853
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Monitoring of Child and Adolescent Patients on Atypical Antipsychotics by Psychiatrists and Primary Care Providers

Abstract: Background: Antipsychotic drug use in children has doubled from 2001 to 2007 with concomitant increase in obesity. Second-generation antipsychotic (SGA) medication use is associated with weight gain, metabolic derangements, and blood sugar and lipid abnormalities in children. The American Psychiatric Association and the American Diabetes Association have recommended metabolic monitoring guidelines for patients using SGA. Study Question: The study object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Although previous studies have shown differences in monitoring frequencies in children treated with antipsychotic drugs, it is clear that the monitoring frequencies were suboptimal (13,15,16,18). Overall, it has been shown that the physical parameter weight was monitored more frequently in children treated with antipsychotic drugs compared to the laboratory parameters glucose and lipids, and waist circumference was monitored much less, which is in line with the results of this current study (14,15,19).…”
Section: Discussionsupporting
confidence: 89%
“…Although previous studies have shown differences in monitoring frequencies in children treated with antipsychotic drugs, it is clear that the monitoring frequencies were suboptimal (13,15,16,18). Overall, it has been shown that the physical parameter weight was monitored more frequently in children treated with antipsychotic drugs compared to the laboratory parameters glucose and lipids, and waist circumference was monitored much less, which is in line with the results of this current study (14,15,19).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are generally in line with those found by previous studies, with generally low monitoring of glucose and lipid profiles, and more adequate monitoring of weight and blood pressure, although there was still room for improvement. 16 , 19 , 26 Self-reported monitoring rates have been found to be higher, 34 36 but this could reflect socially desirable responding of prescribing clinicians in these studies. Our findings indicate that laboratory assessments are often omitted, which is undesirable because of the risk of developing metabolic conditions such as diabetes, because of not catching any abnormalities in time.…”
Section: Discussionmentioning
confidence: 71%
“…Fifteen papers were identified for inclusion in this review comprising four studies of self-reported clinical practice (Curtis et al, 2012;McLaren et al, 2017;Rodday et al, 2015;Walter et al, 2008) (Table 1), five data linkage studies of metabolic monitoring in children and adolescents attending mental health services (Connolly et al, 2015;Hayden et al, 2019;Morrato et al, 2010;Okumura et al, 2018;Raebel et al, 2014) (Table 2) and six retrospective chart review studies to examine metabolic monitoring (Cotes et al, 2017;Coughlin et al, 2018;Featherston et al, 2018;Javaheri and McLennan, 2019;Kauffman et al, 2018;Wakefield et al, 2019) (Table 3). Of the 11 studies which reported data from child and adolescent patients, five provided information about the diagnoses of the children (Connolly et al, 2015;Coughlin et al, 2018;Featherston et al, 2018;Hayden et al, 2019;Morrato et al, 2010).…”
Section: Resultsmentioning
confidence: 99%